The relationship between EFL teachers' professional identity, professional self-esteem, and job satisfaction - Achame Haile Awaje; Hailom Banteyerga Amaha (College of education, Bahir Dar University, 2023)
This study investigated the relationship between secondary school English as a foreign language (EFL) teachers' professional identity, professional self-esteem, and job satisfaction in the Sidama National Regional State, Ethiopia. For this purpose, ninety-four (N=94) EFL teachers were selected from 10 government secondary schools. Schools and participants were selected using cluster and availability sampling techniques respectively. Adapted professional identity, professional self-esteem, and job satisfaction questionnaires were used. The relationship between the variables was examined via the Pearson correlation coefficients. In addition, structural equation modelling (SEM) was applied to test the direct and indirect effects of professional self-esteem and job satisfaction on professional identity. The analysis of the goodness of fit indices yielded a good model fit. The results of correlational analysis indicated that professional self-esteem (r= 0.81, P= 0.000) and job satisfaction (r= 0.70, P= 0.000) are positively and significantly correlated with professional identity. SEM analysis also indicated that professional self-esteem positively predicted professional identity (β= 0.66, P ≤ 0.001). Congruently, job satisfaction positively predicted professional identity (β= 0.27, P≤ 0.001). Moreover, professional self-esteem indirectly mediated the relationship between job satisfaction and professional identity. Thus, it is recommended to pay a close attention to EFL teachers' professional identity and some of the interplaying variables.